China : Economic Reform and Macroeconomic Management - Szapary, Gyorgy (Occasional Papers; Occasional Paper, 1991)
China encountered problems preserving economic stability while pursuing reforms aimed at increasing its economic flexibility and efficiency. This paper examines China's experience with market-oriented reforms since 1978, offering lessons for other centrally planned economies in the midst of transition to free markets.